การพัฒนาต่อยอดธุรกิจองค์กรฟาร์มไก่ไข่ของบริษัท พลวิทยาฟาร์ม จำกัด - เตียวศิริมงคล นันทวัฒน์; ดาวสดใส ไพบูลย์ (MBA-KKU Journal, 2017)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาความคิดเห็นและประสบการณ์ของผู้ที่มีส่วนได้ส่วนเสีย สำหรับการต่อยอดธุรกิจของบริษัท พลวิทยาฟาร์ม จำกัด 2) พัฒนาแผนกลยุทธ์โครงการต่อยอดธุรกิจ และ 3) เพื่อดำเนินงานต่อยอดธุรกิจและประเมินผลความสำเร็จของโครงการ ซึ่งทำการวิจัยร่วมกับการปฏิบัติการจริงโดยการใช้ทฤษฎีสุนทรียสาธกเป็นเครื่องมือในการเก็บรวบรวมข้อมูล จำนวน 153 คน ได้แก่ ผู้ถือหุ้น พนักงาน ลูกค้า ผู้จัดหาวัตถุดิบ ชุมชนของบริษัท พลวิทยาฟาร์ม จำกัด โดยการใช้หลักการสุนทรียสาธกในการสัมภาษณ์ เพื่อรวบรวมข้อมูลนำไปสู่การวิเคราะห์ข้อมูลเพื่อพัฒนาธุรกิจและการวางแผนโครงการต่อยอดธุรกิจ โดยใช้การวิเคราะห์สออ่าร์ ข้อมูลที่ได้จากการศึกษา พบว่า ปัจจัยที่สำคัญในการพัฒนาต่อยอดธุรกิจ ได้แก่ การแปรรูปมูลไก่ไข่สดเป็นปุ๋ยอินทรีย์/สารปรับปรุงดินสามารถเพิ่มรายได้ และช่วยลดกลิ่นเหม็นจากมูลไก่ไข่สด ลดแหล่งแมลงวันซึ่งเป็นไปตามหลักการการวิเคราะห์สออ่าร์ ผู้วิจัยได้ศึกษาความเป็นไปได้ในการวางแผนธุรกิจและดำเนินการลงทุนโรงงานผลิตปุ๋ยอินทรีย์/สารปรับปรุงดิน ภายใต้ผลิตภัณฑ์เบนซ์ตราดาว พบว่ามีการใช้เงินลงทุนรวมทั้งสิ้น 15,017,000 บาท จากการวิเคราะห์ความเป็นไปได้ในด้านการตลาด (กำหนดรายได้เป้าหมาย 2,100,000 บาทต่อเดือน) ด้านการผลิต ด้านการจัดการ และด้านการเงิน พบว่า มีมูลค่าปัจจุบันสุทธิของการลงทุนในโครงการ 3 ปี เท่ากับ 13,183,033 บาท ซึ่งมีค่าเป็นบวก มีผลตอบแทนภายในโครงการของมูลค่าปัจจุบันเท่ากับร้อยละ 18.87 และมีระยะเวลาในการคืนทุน 1 ปี 3 เดือน 27 วัน Abstract The objectives of this research were to 1) study opinions and experiences of stakeholders regarding best practice in business extension development of Pholvithayafarm Company Limited 2) develop strategies of business extension project of the company, and 3) run business extension project and evaluate succession of the project. This study was an action research together with actual operation to find the best experience in successful operation through Appreciative Inquiry (AI). AI technique interview were conducted with 153 stakeholders; shareholders, staffs, customers, suppliers, and community of the company. The data were collected and analyzed by using SOAR, for planning to development project of business extension. The study found that current important factor for business extension was producing organic fertilizer/soil substances from fresh chicken manure to increase income and could also solve stench problem and fly breeding source which was in line with SOAR Analysis. Then, researcher had planned business feasibility and invested business of organic fertilizer/soil substances factory under the Brand name Star benz products. The business feasibility showed that total investment was 15,017,000 baht. It was feasible in market (targeted income 2,100,000 baht per month), manufacture, management, and finance aspect. The Net Present Value (NPV) in 3-year project was positive at 13,183,033 baht. Internal Rate of Return (IRR) was 18.87%. Payback Period was 1 year 3 months and 27 days.